Sífilis na gestação: desafios diagnósticos, terapêuticos e assistenciais no período perinatal e parto. - Isabela Corali Ribeiro; Isadora Neves Tasso; Ana Lúcia de Castro Rodrigues (Revista ft, 2026)
Syphilis in pregnancy is a re-emerging sexually transmitted infection and a sensitive marker of the quality of antenatal care, since congenital syphilis is a preventable event through timely, low-cost diagnosis and treatment. This study aimed to analyse, through an integrative literature review, the diagnostic, therapeutic and care-related challenges of syphilis in pregnancy during the perinatal period and delivery, contrasting the international, national (by macro-region) and local realities, with emphasis on the municipality of Franca, State of São Paulo, Brazil. This is an integrative review, with a descriptive approach, grounded in reference obstetric works and official protocols, complemented by epidemiological studies with international scope (United States, China, Colombia and the African region), national and local scope, as well as secondary data from the Notifiable Diseases Information System (SINAN) and DATASUS. Results showed a sustained rise in gestational syphilis detection rates in Brazil, reaching 35.4 cases per 1,000 live births in 2024, and a congenital syphilis incidence of 9.6 cases per 1,000 live births. The State of São Paulo showed a gestational detection rate above the national figure (44.6/1,000), while Franca, in its municipal series, recorded a predominance of late diagnosis and a high proportion of untreated partners. Internationally, a resurgence of congenital syphilis was observed in the United States, progress in the integrated Chinese programme, and persistence of high prevalence in Sub-Saharan Africa and Latin America. The discussion organised the findings into four axes: factors related to the pregnant woman and partners; to public-network care; to hospital care at delivery; and to newborn follow-up in primary care. It is concluded that the persistence of congenital syphilis stems less from technological limitations and more from care-process failures — late diagnosis, inadequate or incomplete treatment, failure to treat partners, and fragile follow-up — requiring qualification of antenatal care, integration between points of care, and continuing education of health teams.